Variasi Gaya Mengajar Guru Pada Anak Berkebutuhan Khusus di SLB Negeri 1 Kulonprogo - Linda Kurniawati; Nisa Salsabila; Hendy Pratama; Difa Ul Husna Husna (PT. ALHAFI BERKAH INDONESIA, 2024)
This research examines the application of variations in teacher teaching styles to children with special needs at SLBN 1 Kulonprogo. And this research is qualitative research with a descriptive approach. The subjects of this research are teachers with physical impairments, teachers with intellectual disabilities and teachers with hearing impairments. The data collection techniques used are observation and interviews. Data analysis techniques, namely data reduction, data display and concluding drawing/verification. The results of this research show that in this school the application of various teacher teaching styles for children with special needs has not been implemented perfectly because, many teachers still have problems with the use of media, or from their own students.